Rapid and noninvasive assessment of adductor muscle performance through shell-closing strength of Zhikong scallop Chlamys farreri - Xiangyi Zeng; Zujing Yang; Mingyi Sui; Zhi Liu; Qiang Xing; Liping Hu; Liming Jiang; Zhenmin Bao; Xiaoting Huang (Aquaculture Reports)
Shell-closing strength (SCS) is a crucial trait of adductor muscle closely associated with the bivalve's swimming ability and health status. However, the investigation and practical application of SCS have been seriously hampered due to the limited availability and complexity of current measurement methodologies. In this study, a rapid and noninvasive method was developed to quantify SCS with four indicators including total force (TF), time of shell closing (TSC), average force (AF), and maximum force (MF) using a self-developed force gauge device. The optimal measurement time and distance for SCS were three minutes and 0.75 cm, respectively. For ten SCS tests, the coefficients of variation (CV) for all four indicators were between 2.54 % and 5.57 %, and the intraclass correlation coefficients (ICC) exceeded 0.75 in each case, which proved that the measurement results were stable and reliable. Subsequent analysis revealed that the four SCS indicators of scallops were significantly associated with the adductor muscle weight (AMW) and the adductor muscle glycogen content (AMG). The correlation coefficients with AMW were 0.609, 0.258, 0.586, and 0.467 for TF, TSC, AF, and MF, respectively (P < 0.05). For AMG, the correlation coefficients were 0.586, 0.372, 0.506, and 0.334 for TF, TSC, AF, and MF, respectively (P < 0.01). The SCS indicators were then used in a ridge regression multivariate linear model to estimate the contents of AMW and AMG in scallops, yielding coefficients of determination (R2) of 0.81 and 0.87, respectively. Furthermore, scallops with stronger SCS were proved to have longer survival times under heat stress, with correlation coefficients ranging from 0.455 to 0.619 (P < 0.01). This finding indicated that SCS could serve as a reliable metric for assessing the heat resistance of scallops. In conclusion, this study provides a quick, accurate, and noninvasive method for measuring the SCS, which could be useful for the evaluation of adductor muscle performance and the selection breeding of scallops for enhanced quality and resistance traits.